"Temporal Intensification" At the narrative, character and event level "A Study of selected Novels from the Experience of Ibrahim Nasrallah" (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
This research deals with the study of the temporal intensification and the mechanisms of employing psychological time in some of the novels of the writer Ibrahim Nasrallah, in order to identify its forms and its artistic and semantic dimensions at the scriptural - imaginary and factual/real levels,and to highlight its importance in shaping the narrative character and intensifying the event.   The novel development has led to multiple plots and to the deepening in character consciousness, which necessitated neutralizing the story time and intensifying psychological time through the stream of unconsciousness. The narrative time was affected by the character’s concern and confusion, and the plot also became confused, difficult to identify and the narrative appeared to be successive of unspecified target.   Some novelists have become interested in monitoring the depths of the character and detecting its psychological complexities and changeability through intensification of time in its consciousness and deepening the overwhelming feeling of the lived moment. Hence, the psychological time prevailed in many novels that address the social and political situations and the crisis of the intellectual and others ...,   Psychological time has emerged in the monologues of characters and their implications, deep, evident, growing with the moment of the event.  The writer Ibrahim Nasrallah is one of the novelists who took care of the issues of reality, and monitored the depths of the souls burdened with worries, in an attempt to explore the dimensions of reality and the prospect of the horizon of the future.